Effect Of 5% Binahong Leaves Extract Gel On Minor Recurrent Aphthous Stomatitis - Diana, Nur; Prasiska, Intan (IIUM Medical Journal Malaysia, 2017)
Introduction: Recurrent aphthous stomatitis (RAS) is recurrent oral ulcers. RAS pain make patient difficult to speak, eat, swallow, and lowered patient’s quality of life. Binahong leaves is a traditional medicine that has anti-inflammatory, antibacterial, covering agents and antioxidants effect that can be used to cure RAS. The purpose of this study was to determine the effect of binahong leaves extract gel for minor RAS healing. Materials and Methods: This study was an experimental study with pretest-posttest control group design which involved 20 RAS patients visiting USU Dental Hospital. Data collected by initial examination then controlled every day for the next three days. Pain scale is measured with visual analog scale. Erythematous halo is measured by the presence or absence of erythema. Ulcer size is measured by measuring the largest diameter of ulcer. Patient was asked to apply the extract thinly with cotton bud. Analysis of the data used Friedman Test and Cochran Test to determine the difference before and after treatment. Results: The result showed significant reduction in pain scale p = 0.001 (p<0.05), erythema halo p = 0.001 (p<0.05), and ulcer size p = 0.001 (p<0.05). There is a reduction in pain scale, erythema halo, and ulcer size at the time of initial examination to first, second and third control. Conclusion(s): The use of 5% binahong leaves extract gel was effective to reduce pain, erythema halo, and ulcer size of minor RAS.